Moving Forward, Looking Back: On the Frontlines of Dietary Shift in Rural Ecuador - Joan Gross; Carla Guerrón Montero; Peter Berti; Michaela Hammer (Íconos)
Within the broader context of the global nutritional transition, in this article we examine local dietary practices in the northern highlands of Ecuador drawing on ethnographic research. The results of this study demonstrate that the communities studied continue to prepare whole foods for the most part. However, processed foods are also desired and consumed in some households in the area. Finally, we discuss two discourses that motivate dietary choices in this region: nostalgia and cosmopolitanism.